Association Between Alexithymia, Social Support, and Duration of Methamphetamine Use Among Male Methamphetamine-Dependent Patients - Cui, Shu; Cheng, Fangshuo; Yuan, Qiuyu; Zhang, Ling; Wang, Lei; Zhang, Kai; Zhou, Xiaoqin (Frontiers in Psychiatry, 2021)
Abstract： Introduction: China has 1.18 million methamphetamine abusers. Methamphetamine is the illegal drug with the highest abuse rate in China. However, the incidence of alexithymia, the total duration of methamphetamine dependence, social support, and the relationships between them among methamphetamine-dependent patients in the Chinese population have been rarely reported. Methods： A total of 113 methamphetamine-dependence patients (all male, mean age 30.45±3.81 years) were enrolled in the study. General demographic data were collected. Alexithymia and social support were measured by Toronto Alexithymia Scale and Social Support Rating Scale. Results： Duration of methamphetamine use among Chinese male methamphetamine-dependent patients in compulsory detoxification was 8.01 ± 3.80 years on average, 23% (26/113) methamphetamine-dependent patients were considered to have alexithymia personality traits. Compared with short-duration methamphetamine-dependent patients (≤8 years), long-duration methamphetamine-dependent patients (> 8 years) were characterized by older age, higher incidence of alexithymia, less subjective social support and support availability, and greater difficulty in identifying feelings. The results of correlation analysis and multiple linear regression analysis indicated that the total duration of methamphetamine use was positively correlated with difficulty in identifying feelings, but negatively correlated with subjective social support. Conclusions： This cross-sectional study provides support for an association between the duration of methamphetamine use and difficulty in identifying feelings or subjective social support. Although the causality is still unclear, this finding should be considered in the psychotherapy of methamphetamine rehabilitation.